Sosialisasi Gemarikan (Gemar Makan Ikan) sebagai Bentuk Dukungan Pencegahan Stunting pada Anak Usia Sekolah di SDN 3 Mrican, Kediri - Mazaya, Amalia Febryane Adhani; Nurkhasanah, Anissa Aprillia; Cahya, Muhamad Dwi; Maulidiyah, Vika (Penerbit Widina, Widina Media Utama, 2025)
Stunting is defined as disturbances in growth and development that occur in children as a result of poor nutrition, recurrent infections or inadequate psychosocial stimulation. The government program that is in line with stunting prevention is through Gemarikan (Gemar Eating Fish) which is aimed at all groups from children to adults with aim to increase fish consumption to support the body's immune system and as an important source of animal protein for society. Elementary age is the right age to implement good habits, including getting used to eating nutritious food. This socialization aims to provide education to grade 3 elementary school students about the importance of eating fish so that they understand its benefits and start getting used to consuming fish in their daily lives. Community service was carried out using a qualitative approach to grade 3 students at SDN 3 Mrican, Kediri, as many as 16 students in one class. The implementation of community service will be carried out on Monday, September 30 2024. The activity procedure is to carry out interactive dialogues and presentations as well as two-way questions and answers to the audience using presentation slides and interesting videos. The results of the analysis of observations of service activities were then processed and presented in the form of percentages regarding several parameters, namely participant enthusiasm (3rd grade students at SDN 3 Mrican) of 62.5%, understanding of 100% and audience/student follow-up from the activities carried out of 68.75%.ABSTRAKStunting pengertian gangguan pada pertumbuhan maupun perkembangan yang terjadi pada anak sebagai akibat dari gizi buruk, infeksi berulang maupun stimulasi psikososial yang tidak memadai. Program pemerintah yang selaras dengan pencegahan stunting adalah melalui Gemarikan (Gemar Makan Ikan) yang ditujukan pada semua kalangan mulai dari anak-anak hingga dewasa dalam rangka meningkatkan konsumsi ikan untuk mendukung daya tahan tubuh dan sebagai sumber protein hewani penting bagi masyarakat. Usia dasar adalah usia yang tepat untuk menerapkan kebiasaan baik termasuk membiasakan makan makanan bergizi. Sosialisasi ini bertujuan untuk memberikan edukasi kepada siswa kelas 3 SD tentang pentingnya makan ikan agar mereka memahami manfaatnya dan mulai membiasakan konsumsi ikan dalam kehidupan sehari-hari. Pengabdian masyarakat dilakukan dengan pendekatan kualitatif kepada siswa kelas 3 SDN 3 Mrican, Kediri sebanyak 16 siswa dalam satu kelas. Pelaksanaan pengabdian masyarakat dilakukan pada Senin, 30 September 2024. Prosedur kegiatan adalah dengan melakukan dialog interaktif dan presentasi serta tanya jawab dua arah kepada audience menggunakan slide presentasi dan video yang menarik. Hasil analisis observasi kegiatan pengabdian ini kemudian diolah dan disajikan dalam bentuk presentase mengenai beberapa parameter yakni antusiasme peserta (siswa kelas 3 SDN 3 Mrican) sebesar 62,5%, pemahaman sebesar 100% dan tindak lanjut audience/siswa dari kegiatan yang dilakukan sebesar 68,75%.